Effects of Ergonomic Intervention on Musculoskeletal Complaints and Fatigue in the Abaca Banana Fibre Carpet Industry - Setiawan, Heri; Budiyanto, Tri (Spektrum Industri, 2026)
Traditional fibre-based craft industries contribute substantially to employment and community welfare, yet their highly manual production processes often expose workers to significant ergonomic hazards. In the Abaca banana fibre carpet industry, tasks such as fibre extraction, cleaning, drying, sorting, spinning, weaving, and finishing require repetitive movements, prolonged awkward postures, and sustained physical effort, thereby increasing the risk of musculoskeletal complaints and work-related fatigue. This study evaluated the effects of ergonomic intervention on musculoskeletal complaints and fatigue among workers in this industry. This intervention study included 152 workers selected through stratified random sampling and grouped according to the principal production stages. Ergonomic risk was evaluated using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA), musculoskeletal complaints were assessed using the Nordic Body Map (NBM), and fatigue was measured using the Borg Rating of Perceived Exertion scale. Assessments were performed one month before the intervention and repeated at follow-up after the intervention. At baseline, workers demonstrated moderate-to-high ergonomic risk, with mean RULA scores ranging from 4.6 to 4.9 and mean REBA scores ranging from 5.2 to 5.6. Musculoskeletal complaints and fatigue were also reported at moderate levels, with mean NBM scores ranging from 43.4 to 47.6 and mean Borg scores ranging from 10.9 to 11.2. Post-intervention analysis showed significant reductions in all outcome measures (p < 0.05), indicating improvements in ergonomic risk exposure, musculoskeletal complaints, and perceived fatigue across production stages. The findings suggest that ergonomic intervention is an effective approach for improving worker health in traditional craft-based industries. Integrating ergonomic measures into manual production systems may help reduce physical burden, enhance occupational well-being, and support sustainable productivity.